DEVELOPING PANCASILA AND CITIZENSHIP EDUCATION LEARNING MODEL BASED ON CHARACTER EDUCATION THROUGH COMPREHENSIVE APPROACH - Joko Wahono; Intan Kusumawati; Ahmad Nasir Ari Bowo (International Journal of Educational Management and Innovation, 2021)
Education aims to educate and create the nation's future generation with character. However, problems like brawls, violence, abuse of narcotics, illegal drugs, and promiscuity still occur among students. It becomes the concern of parents and teachers in educating and leading students to develop their character. The teacher is obligated to develop Pancasila and Citizenship Education learning models suitable for students to have good character. Through character education, it hoped that it would produce a sound generation. The educational process that gives birth to the expected character is, of course, gradual. This study aimed to find out Pancasila and Citizenship Education learning models for developing students' character. Research using mixed methods research with data collection, analysis, and mixing both quantitative data and qualitative. This study used quantitative and qualitative approaches in collecting data through interviews and questionnaires. The results showed that Pancasila and Citizenship Education Learning model based on character education through a comprehensive approach could develop and shape the students' character, such as inculcation, modeling, values facilitation, and skill-building. Through character development, it hoped that good characters were expected to form permanently.